Mari belajar Bahasa Melayu siri 1 - Nahar, Nora Azian; Nazir, Faridah; Ismail, Mohamad Zuber (SYFE Management Sdn.Bhd., 2020)
This book is produced to provide an overview of the acquisition of knowledge and skills of learning the Malay language to anyone interested. This book can serve as a guide to learn the basic things in the Malay language oral proficiency (listening and speaking) and to learn the basics of writing (reading and writing) using the Malay language.